Safety Climate and Motivation as Predictors of Safety Behaviours in Malaysia's Electrical Industry - Ahmad, Saifuddin; Mohd Tobi, Siti Uzairiah; Abd Rahim , Noorlizawati; Awang, Zainuddin (Journal of Techno-Social, 2026)
Although safety behaviour is vital for preventing fatalities in high-risk industries such as the electrical utility sector, the extent to which organisational factors influence these behaviours remains unclear. This study investigates the impact of safety motivation and safety milieu on employees’ safety behaviours within Malaysia’s largest electrical utility organisation, focusing on both regulatory compliance and active participation in safety initiatives. Grounded in motivational theories, behavioural safety models, and organisational climate theory, this research explores how personal drive and safety perceptions shape workplace behaviour. A quantitative research approach was adopted, employing a structured questionnaire to assess six dimensions of safety climate: supervision, focus on safety, communication and feedback, recognition, coworker support, and training. Safety motivation, comprising both intrinsic and extrinsic aspects, and safety behaviours, including compliance and participation, were measured concurrently. Data were analysed using IBM-SPSS-AMOS 24.0. The Confirmatory Factor Analysis (CFA) procedure was conducted to validate the constructs for validity and reliability and Structural Equation Modelling (SEM) procedure was employed to model and estimate the interrelationship parameters among the constructs in the structural model. The study found supervision, communication, and training are significant predictors of safety motivation, leading to greater compliance and proactive engagement in safety initiatives. Co-worker support and recognition also contributed, albeit indirectly. Academically, the study extends existing safety climate literature by clarifying the mediating role of motivation in linking organisational climate to employee behaviour. Practically, the findings highlight that supervisory support, transparent communication, and continuous training are crucial strategies for fostering a positive safety climate and promoting safer workplace behaviours in Malaysia’s energy sector.